Janus-type emission from a cyclometalated iron(iii) complex - Steube, Jakob; Kruse, Ayla; Bokareva, Olga S.; Reuter, Thomas; Demeshko, Serhiy; Schoch, Roland; Argüello Cordero, Miguel A.; Krishna, Athul; Hohloch, Stephan; Meyer, Franc; Heinze, Katja; Kühn, Oliver; et al. (Nature chemistry, 2023)
Although iron is a dream candidate to substitute noble metals in photoactive complexes, realization of emissive and photoactive iron compounds is demanding due to the fast deactivation of their charge-transfer states. Emissive iron compounds are scarce and dual emission has not been observed before. Here we report the Fe III complex [Fe(ImP) 2 ][PF 6 ] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazol-2-ylidene)), showing a Janus-type dual emission from ligand-to-metal charge transfer (LMCT)- and metal-to-ligand charge transfer (MLCT)-dominated states. This behaviour is achieved by a ligand design that combines four N -heterocyclic carbenes with two cyclometalating aryl units. The low-lying π * levels of the cyclometalating units lead to energetically accessible MLCT states that cannot evolve into LMCT states. With a lifetime of 4.6 ns, the strongly reducing and oxidizing MLCT-dominated state can initiate electron transfer reactions, which could constitute a basis for future applications of iron in photoredox catalysis. Noble metals dominate the field of photosensitizers and luminophores. Now, an approach incorporating cyclometalating and carbene functions into Fe III complexes has been shown to enable dual emission from the opposing ligand-to-metal and metal-to-ligand charge-transfer states. The latter shows an exceptionally long lifetime of 4.6 ns and is quenched by oxygen and other quenchers.